Opportunities in ASEAN-EU economic cooperation - Paderon, Marissa Maricosa A (Archīum Ateneo, 2020)
The European Union (EU) is a dialogue partner of the Association of Southeast Asian Nations (ASEAN) since 1977. This dialogue partnership was institutionalized with the signing of the ASEAN-EEC Cooperation Agreement on 7 March 1980. After that, the EU-ASEAN dialogue relations has grown and expanded in scope and depth. From the limited issues of trade, investment and development cooperation, its partnership has extended to social and cultural affairs; and political and security dialogue. The findings indicate that the ASEAN and EU are ‘natural trading partners’ and should pursue a region-to-region FTA. But an ASEAN-EU FTA is not an easy process given the lack of regional institutional structure and processes in ASEAN coupled with the diversities within the region.